Research for universal health coverage: setting priorities for policy and systems research in Uganda - Freddie Ssengooba; Aloysius Ssennyonjo; Elizeus Rutebemberwa; Timothy Musila; Suzanne Namusoke Kiwanuka; Enid Kemari; Milly Nattimba (Global Health Action)
Background There is international consensus on the need for countries to work towards achieving universal health coverage (UHC) whereby the population is given access to all appropriate promotive, preventive, curative and rehabilitative services at affordable cost. The World Health Organisation (2013) urges all countries to undertake research to customise UHC within national development agendas. Objective To describe the process used to prioritise UHC within the health systems research and development agenda in Uganda. Methods Two national consultative workshops were convened in May and August 2015 to develop a UHC research agenda in Uganda. The participants included multisector representatives from local, national, and international organisations. A participatory approach with structured deliberations and multi-voting techniques was used. Stakeholders’ views were analysed thematically according to health systems building blocks, and multi-voting was used to assign priorities across themes and sub-themes. The priorities were further validated and disseminated at national health sector meetings. Results Of the 80 invited stakeholders, 57 (71.3%) attended. The expressed priorities were: 1) health workforce; 2) governance; 3) financing; 4) service delivery, and 5) community health. The participants also recommended crosscutting research themes to address the social determinants of health, multisectoral collaboration, and health system resilience to protect against external shocks and disease epidemics. Conclusion Discussions that capture the diverse perspectives of stakeholders provide a way of exploring UHC within health policy and systems development. In Uganda, attention should be paid to the principal challenges of mobilising financial and technical capabilities for research and strengthening the link between evidence generation and policy actions to achieve UHC.